ANALISIS PERFORMA TAKEOFF PADA PESAWAT ATR 72 DALAM PENGARUH TAILWIND - Dwiki Fahreza Andreanto; Mufti Arifin; Freddy Franciscus; Evi Endarti (Jurnal Teknologi Kedirgantaraan, 2023)
Information on weather conditions is needed to support flight safety, especially in the process take-off. One of the required weather information is wind data, wind direction and wind speed. One of the wind components is the tailwind(wind from behind). In the small airports it can only be visited by aircraft such as ATR72 and its kind, due to the limited availability of runways and currently many of these airports are still using landing and take-off in the direction of thewind. This can result in a lack of lift during take-off during the tailwind conditions. To prevent this from happening, there is a reduction in the capacity of the aircraft. The purpose of this study was to analyze the performance of the ATR72 aircraft during take-off with tailwind conditions. By calculating the takeoff under normal conditions on the ATR72 aircraft then varying the tailwind speed. The results obtained are the value of the ground roll distance  (????????) and the reduction in aircraft weight (????) at the time of tailwind. a speed tailwind of 0 or normal, obtained a distance of ground roll 849 m, take-off weight of 20948 kg, reduction in aircraft weight of 0. Speed tailwind of 5 kts, distance of ground roll 773 m, take-off weight of 20333 kg, reduction in aircraft weight of 615 kg, while speed of tailwind 10 kts obtained distance of ground roll 697 m, take-off weight of 19308 kg, reduction in aircraft weight of 1640 kg, and speedtailwind of 15 kts, distance of ground roll 621 m, take-off weight of 18225 kg, was obtained. reduction in aircraft weight by 2723 kg.